326. REDUCTION OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY WITH RETROSTERNAL GASTRIC TUBE RECONSTRUCTION. (24th September 2022) - Okumura, Tomoyuki; Miwa, Takeshi; Numata, Yoshihisa; Watanabe, Toru; Hirano, Katsuhisa; Igarashi, Takamichi; Tanaka, Haruyoshi; Hashimoto, Isaya; Shibuya, Kazuto; Hojo, Shozo; Yoshioka, Isaku; Fujii, Tsutomu
Abstract: Anastomotic leakage (AL) after esophagectomy is one of the major complications after esophagectomy. The aim of this study was to evaluate anastomotic procedure to reduce AL after esophagectomy with retrosternal gastric pull up. A total of 157 consecutive patients underwent thoracoscopic esophagectomy followed by retrosternal reconstruction with gastric tube in our hospital between January 2008 and December 2021. The anastomotic procedure was revised at January 2016. After cervical esophagogastric anastomosis using circular stapler, gastric tube was pulled down to linearize and place the anastomotic site below the suprasternal notch (SN). The sternum tracheal distance (STD) and the level of esophagogastric anastomosis (LEA) were measured using CT image. In comparison between the former (-December 2015, 65 cases) and later (January 2016-, 92 cases) group, AL was significantly reduced from 11/65 (16.9%) to 0/92 (0%) cases (p < 0.001). LEA was significantly lower in the later group than former group (2.7 mm below SN vs 25 mm above SN; p < 0.001). No difference was observed in the clinicopathological characteristics. In comparison between the cases with and without AL (11/146 cases), significant difference was seen in BMI (average 24.4/21.6, p<0.01) and LEA (average 23.5/8.0 mm, p = 0.02). Multivariate analysis revealed that BMI (21.5>, p = 0.02) and LEA (0>, p < 0.01) were the independent factors associated to AL. Surgical procedure which avoids excessive compression on the gastric tube at the thoracic inlet may take an important role in reduction of AL.